Perubahan Fungsi Tinggalan Tradisi Megalitik di Desa Bedulu, Kecamatan Blahbatuh, Kabupaten Gianyar - Edi Suantara, I Wayan; Agung Bawono, Rochtri; Palupi Titasari, Coleta (Humanis; Volume 17. No. 2. Nopember 2016, 2016)
Megalithic culture is culture which produces big buildings made of big stone. The megalithic cultural relics are exist in Bedulu Village, Blahbatuh District, Gianyar Regency in form of stone mortar, millstone, menhir, flat stone, natural stone, and sarkofagus. This research was intended to know the function changes of the megalithic cultural relics or heritage in several temples in Bedulu Village, such as: Santrian Temple, Dukuh Santrian Temple, Samuan Tiga Temple, Tegal Penangsaran Temple, Gunung Sari Temple, and the house yard of Gusti Putu Darmi, and also to find out the factors that influence those changes. This research used several data collection methods, data analysis, and theories to support in answering the research problem. The research method used includes data collection by conducting observation, interview, and literature study. The next step was data processing in which the researcher used qualitative analysis, morphological analysis, comparative analysis, and contextual analysis. The theories used to answer the research problem were social changes theory and structural functional theory. The results of the function changes analysis of the megalithic tradition’s relics in Bedulu Village especially in several temples indicate that there was a function change in terms of naming and usability. In terms of naming the changes could be seen from the way how to name the Gods and how to name the celestial bodies. In terms of usability could be seen from the function in which the relics used to be fuctioned as a worshiping pleace for ancestors while nowdays the relics are functioned as mediums to worship to the God (Ida Sang Hyang Widhi Wasa). Those changes were caused by some factors such as, religion factor in which people have already known the God, less information factor from relevant instance, and also ideological factor that is people’s mindset or point of view about archeological heritage or relics especially megalithic relics in the Bedulu Village, Blahbatuh Distric, Gianyar Regency.